2002
DOI: 10.1086/342973
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Patterns of Meiotic Recombination across the Human Major Histocompatibility Complex

Abstract: Definitive characteristics of meiotic recombination events over large (i.e., >1 Mb) segments of the human genome remain obscure, yet they are essential for establishing the haplotypic structure of the genome and for efficient mapping of complex traits. We present a high-resolution map of recombination at the kilobase level across a 3.3-Mb interval encompassing the major histocompatibility complex (MHC). Genotyping of 20,031 single sperm from 12 individuals resulted in the identification and fine mapping of 325… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
212
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(232 citation statements)
references
References 67 publications
20
212
0
Order By: Relevance
“…This is in agreement with a similar lack of evidence for an enhanced recombination rate in the human MHC region. 39 The most important aim of our study was to assess the impact of Mhc class I-genotypes on disease progression in SIV-infected rhesus macaques. Therefore we studied the influence of Mhc class I haplotypes upon disease progression in SIV infection, rather than single gene alleles.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with a similar lack of evidence for an enhanced recombination rate in the human MHC region. 39 The most important aim of our study was to assess the impact of Mhc class I-genotypes on disease progression in SIV-infected rhesus macaques. Therefore we studied the influence of Mhc class I haplotypes upon disease progression in SIV infection, rather than single gene alleles.…”
Section: Discussionmentioning
confidence: 99%
“…The LMP/TAP gene cluster also features a well-characterized recombination hot spot within intron 2 of the TAP2 gene, 33,34 and additional recombination hot spots are located throughout the human MHC locus. 35 Until functional data are found to confirm associations with autoimmune disease suggested by genetic studies, definitive conclusions about genetic association in this region will remain controversial, as associations with autoimmune disease may be due to linkage disequilibrium with other genes in the MHC class II region. It has also been suggested that the action of several MHC genes, including the LMP/TAP genes, might contribute to autoimmune disease pathogenesis, and that statistical analyses might average the linkage of the various genes and identify only polymorphic genes located centrally in the MHC class II region.…”
Section: Discussionmentioning
confidence: 99%
“…LD is the nonrandom association of alleles at adjacent genetic loci and is the result of lack of recombination between loci at meiosis, generally indicating the loci are close together, thus having a low probability of recombination or in the case of LD between distant loci, that the population within which they are found is relatively young (eg Europeans). A further complicating factor is the uneven distribution of meiotic recombination, especially in the MHC, and recent evidence indicates that patterns of LD seen in the MHC are driven chiefly by recombination hotspots rather than population history [131][132][133] and can vary by haplotype. 134 One of the earliest studies of the TNF promoter polymorphisms 135 showed the extent of haplotypes across the MHC.…”
Section: Disease Associations-conclusionmentioning
confidence: 99%